Study on the Blending Characteristics of Ternary Cementless Materials - Yi-Hua Chang; Lukáš Fiala; Martina Záleská; Dana Koňáková; Wei-Ting Lin; An Cheng (Materials Proceedings, 2023)
In this study, three industrial by-products (ultrafine fly ash, ground granulated blast-furnace slag (ggbs) and circulating fluidized bed co-fired fly ash) were used to produce ternary cementless composites without using alkali activators. The finenesses of ultrafine fly ash, ggbs and co-fired fly ash were 33,800, 5830 and 5130 cm2/g, respectively. The composite material was developed by mixing supplementary cementing materials of different particle sizes and exploiting the high-alkaline properties of the co-fired fly ash to develop a substantial hardening property like cement. The test specimens were made in the form of pastes and the water-to-cementitious-material ratio for the test was fixed at 0.55. The test results show that the flowability of the six different mixtures could be up to 120% and the setting time could be controlled within 24 h. At 60% of the ggbs proportion, the setting time could be held for 8 h. The compressive strength of each proportion reached 7 MPa at 7 days and 14 MPa at 28 days. The water-cured specimens exhibited better strength behavior than the air-cured specimens. Scanning electron microscopy found the main components of strength growth of the specimens to be hydrated reactants of C-A-S-H or ettringite. The results of the XRF analysis show that the specimens responded to higher compressive strengths as the Ca/Si and Ca/Al ratios increased.